Development of an Advanced Biology Learning Website in the Fields of Biotechnology, Biochemistry, and Biomedicine with the STEAM Approach - Susanto, Hendra; Ibrohim; Basuki, Andi; Fadzil, Hidayah Mohd; Syafruddin, Afis Baghiz; Gunawan, Ari (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The growing industry has given birth to various innovations, one of which is the emergence of three new branches of knowledge in biology: biotechnology, biochemistry, and biomedicine. However, this branch of science has not been explored in biology education for students. Technology, in the form of online learning platforms, can address current challenges. STEAM-based biology learning can increase student engagement, motivate creative exploration, and stimulate critical thinking. This study aims to develop an advanced biology learning platform and test the feasibility of the learning media. This study follows the analysis, design, development, implementation, and evaluation (ADDIE) model. The results of this study have led to the development of the “Advanced Biology” website, which contains various exciting features for students. This feature includes a homepage display, learning content display, case-based learning, and research project display. This platform provides engaging educational videos and comprehensive learning materials. The case studies on this site offer an overview of problem-solving and the current state of the industry. This media validates learning materials, media, and technology in the ideal category.